Universalistisches Ideal und koloniale Kontinuitäten Die »harkis« in der Fünften Französischen Republik - Laiß, Anna (Pariser Historische Studien, 2021)
When Algeria gained independence in 1962, an estimated 1 million European settlers and roughly 85 000 so called »Harkis«, muslim Algerians that served as auxiliaries in the French Army, left Algeria en route to France. Were the »Harkis« received as »traitors of the Algerian nation«, as »French citizens with rights to repatriation« or were they seen simply as »refugees«? Anna Laiß provides insightful analysis into the controversial perceptions and portrayals that dominated the "Harkis« existence, and that of their descendents, in their search for a place in the French Republic. She reveals the areas of conflict and discord between the French ideals of republican universalism and the colonial mindset and behaviour, which are to be found in debates about integration and colonial memory, and which extend well beyond the period of decolonisation.